A new tool to study real dynamics: The convergence plane - Magreñán, Á. Alberto (Applied Mathematics and Computation, 2017)
In this paper, the author presents a graphical tool that allows to study the real dynamics of iterative methods whose iterations depends on one parameter in an easy and compact way. This tool gives the information as previous tools such as Feigenbaum diagrams and Lyapunov exponents for every initial point. The convergence plane can be used, inter alia, to find the elements of a family that have good convergence properties, to see how the basins of attraction changes along the elements of the family, to study two-point methods such as Secant method or even to study two-parameter families of iterative methods. To show the applicability of the tool an example of the dynamics of the Damped Newton's method applied to a cubic polynomial is presented in this paper. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: real dynamics; nonlinear equations; graphical tool; iterative methods; basins of attraction; JCR; Scopus